Availability and utilization of mechatronics facilities in higher institutions in north-central, nigeria: the way forward - Arah, A. S. (International Journal on Human-Computing Studies, 2021)
The implementation of automobile technology education curriculum to produce technological know-how graduates through effective teaching and learning in higher institutions cannot be achieved without the availability and utilization of mechatronics facilities. The paper investigated the availability and utilization of mechatronics facilities in higher institutions in North-Central, Nigeria and the way forward. The paper highlighted on the concept of high institution, mechatronics systems, automotive mechatronics, mechatronic systems facilities, availability and utilization mechatronic systems facilities in high institution as well as way forward in the provision of mechatronic systems facilities in higher institutions. Conclusions were drawn and recommendations include among others, Government should provide adequate facilities to higher institutions workshops using current strategies identified to ensure acquisition of relevant skills, and knowledge and experience that are relevant to the growth of the country